Numerical Extraction of the Equivalent Circuit for a Basic Magnetoelectric Dipole Antenna - Zhiyi Li; Yuzhu Tang; Zhifan Zhao; Linwan Deng; Hongzheng Zeng; Xing Chen (Journal of Electromagnetic Engineering and Science, 2024)
Magnetoelectric dipoles have attracted global research attention due to its broadband, unidirectional, and high front-to-back ratio characteristics. This study implemented a co-simulation between a basic magnetoelectric dipole and its front feeding circuit through the step-by-step numerical extraction of its equivalent circuit model equipped with lumped and frequency-independent components. First, the series resonance subcircuit was derived from the series resonance point in the impedance of the magnetoelectric dipole. Second, the parallel resonance sub-circuit was achieved based on the parallel resonance point. By combining the series and parallel sub-circuits according to the sequence of their resonance frequency, the final form of the equivalent circuit for the basic magnetoelectric dipole was realized. Furthermore, to obtain the component values of the proposed circuit, a numerical fitting technique was adopted to accurately match the input impedance of the antenna and its equivalent circuit. A comparison of the circuit and antenna electromagnetic simulations showed that they agreed well with each other. Hence, the correctness and feasibility of the extraction process were verified. The overall results showed that the proposed circuit model can easily substitute for a basic magnetoelectric dipole in the implementation of antenna/circuit co-simulation in circuit simulators.